Developing a program to increase geropsychology competencies of Veterans Health Administration (VHA) psychologists. Issue 4 (1st October 2020) - Huh, J.W. Terri; Rodriguez, Rachel; Gould, Christine E.; R. Brunskill, Sarah; Melendez, Luis; Kramer, B. Josea
ABSTRACT: There is an alarming supply and demand gap for geropsychology expertise within the United States. Health policy experts called for increasing geriatric mental health competencies for all mental health providers, including within Veterans Health Administration (VHA), to address this problematic gap. The VHA Geriatrics Scholar Program (GSP) Psychology Track was developed because there were no commercially available trainings in geropsychology for licensed psychologists. Developing the GSP Psychology Track was based on an evidence-based educational model for the VHA primary care workforce; and included a stepwise curriculum design, pilot implementation, and program evaluation. The educational program was pilot tested with eight VHA psychologists. Evaluation results demonstrated feasibility of implementing an innovative integrated multimodal educational program in geropsychology. Furthermore, this program was associated with reports of increased confidence in geropsychology competencies and self-reported implementation of geropsychology knowledge, indicating the potential for this educational model to improve mental health care for older Veterans.